ChemInform Abstract: A New Isoflavanol from the Fruits of Kotschya strigosa (Fabaceae). Issue 36 (August 2016) - Awouafack, Maurice D.; Tchuenguem, Roland T.; Ito, Takuya; Dzoyem, Jean P.; Tane, Pierre; Morita, Hiroyuki
Abstract: The isolation of the new isoflavanol named kotstrigoisoflavanol (I) together with three known compounds, is achieved by phytochemical investigation of the fruits of Kotschya strigosa (Fabaceae).